Design of a High-Gain MEMS-Based Microstrip Patch Antenna for RF Energy Harvesting in Millimeter-Wave 5G Applications - Redzuwan R.M.; Sampe J.; Latif R.; Rhazali Z.A.; Yunus N.H.M. (Seventh Sense Research Group, 2025)
The evolution of wireless technology has spurred the development of the Internet of Things (IoT), wearable electronics, and Fifth Generation (5G) systems, often requiring remote sensors that face power supply challenges. Antennas capable of harnessing ambient Radio Frequency (RF) energy has garnered significant attention as a solution to power these sensors, providing an alternative to traditional batteries and solar cells, especially in areas with limited access to sunlight. This paper focuses on designing microstrip patch antennas specifically for capturing RF energy in 28 GHz millimeter-wave (mmWave) 5G networks. The antennas are developed using three distinct substrates: Rogers RT Duroid 5880 (RT-5880), porcelain, and borosilicate glass, each with a consistent thickness of 0.787 mm. The dielectric constants for RT-5880, porcelain, and borosilicate glass are 2.2, 5.6, and 4.4, respectively. The antennas' performance metrics, including return loss (S11), gain, bandwidth, and Voltage Standing Wave Ratio (VSWR), are simulated and evaluated via CST Microwave Studio. The simulation outcomes indicate that all proposed antennas achieve a bandwidth exceeding 0.5 GHz, with RT-5880 at 1.58 GHz, porcelain at 1.73 GHz, and glass at 0.95 GHz. The S11 parameter results show that RT-5880 has -16.4518 dB, porcelain -24.06 dB, and borosilicate glass -33.90 dB, which is a 34.65% improvement as compared to others. Furthermore, borosilicate glass has a higher gain of 7.017 dB, compared to 6.472 dB and 5.475 dB for RT-5880 and porcelain, respectively. The antenna using borosilicate glass shows the best potential for RF energy harvesting in mmWave 5G applications. ? 2024 Seventh Sense Research Group.